On Vladimir Pavlov’s first residential buildings - Grigorieva, Elena; Druzhinina, Inna (project baikal, 2026)
Vladimir Pavlov’s creative activity is internationally known and universally recognized. The architect’s legacy impresses with its innovation and originality of solutions, as well as skillful use of compositional, artistic and engineering techniques that remain relevant to this day. The article presents the results of an in-depth study of the architecture of Pavlov’s first residential buildings, defines the time frame and exact chronology of their construction. The authors reveal the features of urban allocation of facilities, layouts of sections and apartments, constructive and facade solutions.